Worth the Wait? The Effect of Early Term Birth on Maternal and Infant Health - Kasey Buckles; Melanie Guldi (Institute for the Study of Labor (IZA), 2016)
Early term birth is defined as birth at 37 or 38 weeks gestation. While infants born early term are not considered premature, the medical literature suggests that they have an increased risk of serious adverse health outcomes compared to infants born at term (39 or 40 weeks). Despite these known harms, we document a rise in early term births in the United States from 1989 to the mid-2000's, followed by a decline in recent years. We posit that the recent decline in early term births has been driven by changes in medical practice advocated by American College of Obstetricians and Gynecologists recommendations and programs such as the March of Dimes' "Worth the Wait" campaign. We first show that this pattern cannot be attributed to changes in the demographic composition of mothers. We next exploit county-level variation in the timing of these changes in medical practice and show that early term inductions lead to an increased risk of precipitous labor, lower birth weights and an increased risk of birth injury and required ventilation. Our results suggest that reductions in early term inductions can explain about one-third of the overall increase in birth weights for term births between 2010 and 2013.
Keywords: J13; I18; 330; infant health; maternal health; birth weight; induction of labor; early elective delivery